BIDIRECTIONAL FLOW-CONTROLLABLE ARTIFICIAL RESPIRATOR - LEE, Yoon Je; LEE, Jang Woo (2025)
A bidirectional flow-controllable artificial respirator, according to one embodiment, comprises: a chamber for storing air; a tube connected to the chamber and having air flowing therein; a mask connected to the tube and mounted on a face or mouth; and a flow control valve unit provided in the tube and controlling the air flow between the chamber or an air supply source, and the mask. The flow control valve unit comprises: a first valve allowing an air supply path from the air supply source toward the mask; and a second valve allowing an air discharge path from the mask toward the outside of the respirator, wherein the first valve and the second valve are alternately opened and closed during artificial respiration, the first valve is blocked during chest compressions so that negative pressure in a subject receiving air is maintained for a long period, and the first valve and the second valve may be selectively opened and closed so as to allow air to be supplied according to a preset air supplying period.